Intimately coupled hybrid of graphitic carbon nitride nanoflakelets with reduced graphene oxide for supporting Pd nanoparticles: A stable nanocatalyst with high catalytic activity towards formic acid and methanol electrooxidation. (10th May 2016) - Zhang, Wenyao; Yao, Qiushi; Wu, Xiaodong; Fu, Yongsheng; Deng, Kaiming; Wang, Xin
Graphical abstract: Highlights: Intimately coupled hybrid of g-C3 N4 nanoflakelets with rGO is fabricated via an in situ chemical synthesis approach. The detailed forming process of CNNF-G composite is carefully investigated. The Pd-CNNF-G composite exhibits exceptional catalytic activity and durability. The real fuel cells have been assembled to evaluate the performance of the electrocatalysts. The effects of g-C3 N4 nanoflakelets on Pd atom were investigated by DFT computations. Abstract: A novel nitrogen-rich support material (CNNF-G) consisting of graphitic carbon nitride (g-C3 N4 ) nanoflakelets (CNNF) and reduced graphene oxide (rGO) is designed and fabricated for loading Pd nanoparticles. Structural characterizations indicates that the CNNF is formed via splitting decomposition of the g-C3 N4 polymer on rGO at higher temperatures and the resulting CNNF is intimately coupled to the rGO sheets. The CNNF can provide more exposed edge sites and active nitrogen species for the high dispersion of Pd NPs. It is found that the Pd NPs with an average diameter of 3.92 nm are uniformly dispersed on CNNF-G sheets. DFT computations reveal that CNNF can trap Pd adatom and thus act as a Pd nucleation site at which Pd atoms tend to accumulate to form Pd clusters. The Pd-CNNF-G nanocatalyst exhibits excellent electrocatalytic activity for both formic acid and methanol oxidation reactions, including large electrochemically active surface area (ECSA) values, significantly high forward peak current densities, and reliable stability and durability, far outperforming the Pd-graphene, commercial activated carbon-supported Pd catalyst or Pd-carbon nanotubes. Such a stable Pd/CNNF-G nanocatalyst may bring new design opportunities for high-performance direct formic acid fuel cell (DFAFC) and direct methanol fuel cell (DMFC) in the future.